1993
DOI: 10.1136/jech.47.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with constipation in a community based sample of people aged 70 years and over.

Abstract: Study objective-The aim was to determine the prevalence and factors associated with constipation in elderly people.Design-The study was a survey involving administration of a structured questionnaire, an interview, and a dietary assessment.Setting-The survey was community based and the population studied was drawn from the practice records of all five general practitioners serving a rural township of 13 500 people.Participants Mosgiel is served by five family practitioners based at the Mosgiel health centre. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
1
3

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 15 publications
7
53
1
3
Order By: Relevance
“…Here, however, in common with several other studies (Campbell et al, 1993;Towers et al, 1994;Murakami et al, 2006), we failed to find such an association. A possible explanation for this is that the dietary fiber intake of most subjects was too low to have a protective effect.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Here, however, in common with several other studies (Campbell et al, 1993;Towers et al, 1994;Murakami et al, 2006), we failed to find such an association. A possible explanation for this is that the dietary fiber intake of most subjects was too low to have a protective effect.…”
Section: Discussionsupporting
confidence: 78%
“…The favorable effect of dietary fiber on constipation is widely accepted and several (Dukas et al, 2003;Sanjoaquin et al, 2004), although not all (Campbell et al, 1993;Towers et al, 1994;Murakami et al, 2006), observational studies have indicated an inverse relation between dietary fiber intake and constipation. However, while most previous studies have defined constipation according to the infrequency of bowel movement (Campbell et al, 1993;Towers et al, 1994;Dukas et al, 2003;Sanjoaquin et al, 2004) or the subjective perception of patients (Murakami et al, 2006), a consensus definition of constipation consists of straining, hard stools and incomplete evacuation in addition to infrequency (Rome criteria) (Whitehead et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of dietary fiber on constipation is widely accepted, but only a few studies have found an inverse association between dietary fiber and constipation (Dukas et al, 2003;Sanjoaquin et al, 2004), and many other studies have failed to find this association (Everhart et al, 1989;Whitehead et al, 1989;Campbell et al, 1993;Towers et al, 1994). Unexpectedly, there seemed to be a positive association between dietary fiber intake and constipation in the Diet and constipation in Japanese women K Murakami et al present study, although the association disappeared after further adjustment for rice intake, suggesting that the association is largely due to an inverse association between rice intake and constipation.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies in the West, not only various factors including age (Everhart et al, 1989;Sandler et al, 1990;Campbell et al, 1993;Dukas et al, 2003), sex (Everhart et al, 1989;Sandler et al, 1990;Campbell et al, 1993), smoking status (Dukas et al, 2003), alcohol consumption (Dukas et al, 2003;Sanjoaquin et al, 2004), body mass index (BMI) (Sandler et al, 1990;Dukas et al, 2003;Sanjoaquin et al, 2004), and physical activity (Everhart et al, 1989;Sandler et al, 1990;Dukas et al, 2003;Sanjoaquin et al, 2004), but also several aspects of diet such as intakes of energy (Sandler et al, 1990;Towers et al, 1994), dietary fiber (Dukas et al, 2003;Sanjoaquin et al, 2004), and nonalcoholic beverages (Sandler et al, 1990;Sanjoaquin et al, 2004) have been associated with constipation. However, information on this issue is quite limited among people in Asian countries including Japan (Kunimoto et al, 1998;Wong et al, 1999;Nakaji et al, 2002;Fujiwara, 2003), where dietary habits and foods available differ considerably from those in Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…All subjects were European; however, only 2.3% of the older New Zealand population is Maori and most tend to live in the north. Further details of subject selection and characteristics of the baseline population, including nutrient intakes, have been presented elsewhere (Horwath et al, 1992;Campbell et al, 1993aCampbell et al, , b, 1995.…”
Section: Subjects and Study Designmentioning
confidence: 99%